MPKB web-based payroll system / Nor Fadia Ibrahim - Ibrahim, Nor Fadia (2012)
Kota Bharu Municipal Council (MPKB) is an organization under the Government State Council which operates around the town of Kota Bharu. Under MPKB, there is the Department of Finance that is responsible in generate and manage their staffs’ payroll. Currently, the payroll process that including overtime in MPKB is done manually. There are several problems identified through this manual process such as paycheck errors, wrong calculation for overtime, delay payment for allowances, difficulties in searching the details, less secure, and the main problem is at times the organization needs to re-adjust the new salary for the employees due to the changes of salary’s scheme that announced by the government. MPKB Web-Based Payroll system will be developed to overcome the problem and also ease the administrators in performing payroll process. Admin can easily calculate the overtime of employees without need to calculate manually, and then insert the records into payroll system separately. Besides that, the admin can generate pay slip that already include all the calculation without need to calculate by themselves. Also, the admin can remain to use the system if the changes of salary’s schemes occur. The methodology that will be used to develop MPKB Web-Based Payroll system is the waterfall model that goes through phases such as system planning, system analysis, system design, system implementation and system support and security. At the end, it is found out that the system is effective to use, with none of the respondents either disagree or strongly disagree with any of the system’s characteristics. This system should be expanded more by including other types of employees and also should have one features, which is each department can submit the overtime records to the final calculation.